ANALISIS PENGARUH KINERJA LINGKUNGAN DAN PENGUNGKAPAN SUSTAINABILITY REPORTING TERHADAP NILAI PERUSAHAAN - Muhammad Farizal Gigih Putra Pratama; Indah Purnamawati; Yosefa Sayekti (Universitas Jember, 2019)
This study aims to test and analyze environmental performance and sustainability reporting disclosures in manufacturing companies listed on the Indonesia Stock Exchange. This study also aims to determine the effect of environmental performance and sustainability reporting disclosure on firm value. This research uses quantitative research using purposive sampling method. The analytical method used is multiple linear regression with a significance level of 5%. This research was conducted by selecting research data in accordance with the criteria of a sample of 17 manufacturing companies. The data used are secondary data, namely data obtained indirectly from original sources but through internet intermediary media in the form of financial statements of manufacturing companies listed on the Indonesia Stock Exchange and references in the form of supporting books that relate to research. Keywords: Environmental Performance, Firm Value, Sustainability Reporting, Firm Value